A grape seed and bilberry extract reduces blood pressure in individuals at risk of developing type 2 diabetes: the PRECISE study, a double-blind placebo-controlled cross-over intervention study - Grohmann, Teresa; Walker, Alan W.; Russell, Wendy R.; Hoggard, Nigel; Zhang, Xuguang; Horgan, Graham; de Roos, Baukje (Frontiers in Nutrition, 2023)
Background: Type 2 Diabetes Mellitus (T2DM) is a major risk factor for the development of cardiometabolic diseases. T2DM prevention is largely based on weight-loss and whole diet changes, but intervention with dietary plant bioactives may also improve metabolic health. Objective: To assess whether supplementation with bilberry and grape seed extract for 12 weeks improves cardiometabolic outcomes in individuals at risk of developing T2DM, and to determine whether individual treatment response is associated with differences in gut microbiota composition and levels of phenolic metabolites in blood and feces. Methods: In the randomized, double-blind, placebo-controlled, cross-over PRECISE intervention study, 14 participants, aged ≥45 years, with a BMI >28 kg/m2, and having an increased risk of T2DM, received a supplement containing 250 mg of bilberry plus 300 mg of grape seed extract, or 550 mg of a control extract, per day, for 12 weeks each. Blood samples were obtained for the assessment of HbA1c, fasting glucose, oral glucose tolerance tests, insulin, glucagon levels, total, LDL and HDL cholesterol, and phenolic acids. We also assessed advanced glycation end products in the skin, ambulatory 24-hour blood pressure, 7-day dietary intake by weighed food diaries, fecal levels of phenolic metabolites using LC-MS/MS and gut microbiota composition using 16S rRNA gene sequencing analysis. Results: The combined bilberry and grape seed extract did not affect glucose and cholesterol outcomes, but it decreased systolic and diastolic ambulatory blood pressure by 4.7 (p<0.001) and 2.3 (p=0.0009) mmHg, respectively. Eight out of fourteen participants were identified as blood pressure ‘responders’. These responders had higher levels of phenylpropionic and phenyllactic acids in their fecal samples, and a higher proportional abundance of Fusicatenibacter-related bacteria (p<0.01) in their baseline stool samples. Conclusion: Long-term supplementation with bilberry and grape seed extract can improve systolic and diastolic blood pressure in individuals at risk of T2DM. Individual responsiveness was correlated with the presence of certain fecal bacterial strains, and an ability to metabolize (epi)catechin into smaller phenolic metabolites.